PENGARUH TECHNIQUE QUALITY DAN PROCESS QUALITY TERHADAP CUSTOMER SATISFACTION (STUDI KASUS DWELLING TIME PADA TERMINAL PETIKEMAS SEMARANG) - Hertas Fajar Tawakal; Putut Haribowo; Siti Nur Barokah (Politeknik Negeri Semarang, 2017)
The purpose of this research is to analyze the effect of technique quality and process quality on customer satisfaction (a case study of dwelling time in Terminal Petikemas Semarang) The methods used to analyze data are validity test, reliability test, assumption classic test, multiple linear regression method, t-test (partial), f-test (simultaneous), and the coefficient of determination test (Adjusted R2) Based on this research, the result of statistical F-test has significant value < significant level (0,000 < 0,05). It means that technique quality and process quality has a significant impact on customer satisfaction. From the result of coefficient of determination test, adjusted R2 has value of 0,607. It’s mean that the impact of independent variable (technique quality and process quality) toward dependent variable (customer satisfaction) is at 60.7%, while the remaining 39.3% is influenced by other variables that outside in this research.